STUDYING THE EFFECTIVENESS OF ALLERGEN-SPECIFIC IMMUNOTHERAPY (ASIT) FOR ALLERGIC DISEASES (International journal of artificial intelligence, 2026)
Allergen-specific immunotherapy (ASIT) is the most effective method of treating allergic pathology. The method consists in the administration of small doses of the antigen, which was an etiological factor in the development of allergies, and in a particular patient. In this case, the body desensitizes to this antigen. The use of ASIT leads to a reduction in symptoms and the need for treatment and, in addition, has the potential for long-term clinical effect, preventing the development of allergies and its symptoms. Treatment acts on the main immunological mechanisms responsible for the development of clinical symptoms. ASIT is an anti–inflammatory, pathogenetic and preventive treatment of allergic respiratory tract diseases.